Analysis of Students' Mathematical Representation Ability in Terms of Resilience - Fatmasari, Yola; Rustina, Ratna; Herawati, Linda (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2024)
This research aims to describe students' mathematical representation abilities in terms of mathematical resilience. The method used in this research is the descriptive method. Data collection techniques consisted of distributing mathematical resilience questionnaires, mathematical representation ability tests, and interviews. The subjects were selected from 3 students in class VII-G of SMPN 17 Tasikmalaya based on the results of a questionnaire that met one of the categories of high, medium, low and the results of the mathematical representation ability test that met the most indicators of mathematical representation ability without looking at whether the answer was right or wrong. . The data analysis techniques used are data reduction, data presentation, and drawing conclusions. Subjects with high mathematical resilience (S-27) can fulfill six indicators of mathematical representation ability with systematic, detailed answers and correct conclusions. Subjects with moderate mathematical resilience (S-13) can fulfill five indicators of mathematical representation ability but there are errors in calculating and writing units. Subjects with low mathematical resilience (S-16) can meet four indicators of mathematical representation ability with incorrect final answers and errors in understanding algebraic addition.Keywords: Mathematical Representation Ability, Mathematical Resilience.